Precise relative locations for earthquakes in the northeast Pacific region (United States. Department of Energy. ; distributed by the Office of Scientific and Technical Information, U.S. Department of Energy, 2015)
Earthquake Location; Surface Waves; Oceanic Transform Faults; Juan De Fuca; Blanco Transform Fault; Tectonics.
Published through SciTech Connect.
10/09/2015.
"la-ur--15-22679"
Journal of Geophysical Research. Solid Earth 120 10 ISSN 2169-9313 AM.
K. Michael Cleveland; Thomas F. VanDeMark; Charles J. Ammon.
Keywords: Geosciences.